STRATEGY TO IMPROVE LABOR PRODUCTIVITY IN PT FREEPOT INDONESIA’S UNDERGROUND MINING PROJECT - Almuntadzar, Inzi; Maarif, M. Syamsul; Baga, Lukman M. (Jurnal Aplikasi Bisnis dan Manajemen, 2021)
Poor productivity of labor construction causes project cost to increase and project completion schedule behind target. Underground mining company such as PT Freeport Indonesia (PTFI) struggle to overcome problem with productivity. It is critical for mining underground company to keep up labor productivity due to importance of mining production. Therefore, the purpose of this research are: (1) to identify the factors that influence labor productivity; (2) to formulate alternative strategies to increase the productivity; and (3) to formulate recommendations carried out by PTFI in order to increase the productivity. This research use literature review and expert discussion to identify factors affecting labor productivity in the construction industry. The analytical Hierarchy Process (AHP) method used to find the best strategies to increase labor productivity. The result of this research showed that the factors that has the most influence is labor management, the most influencing actor is construction management, the most important goal is to improve project management implementation and the best strategy to increase labor productivity is to create a Project Management Office (PMO) system. The recommendation that can be given is that PTFI needs to develop guidelines and programs for PMO system development and apply PMO to all PTFI mining activity. Keywords: Analytical Hierarchy Process (AHP), Labor productivity, Project Management Office (PMO), Strategies, Underground mining